2016
DOI: 10.1111/imm.12591
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background affects the expansion of macrophage subsets in the lungs of Mycobacterium tuberculosis‐infected hosts

Abstract: SummaryM1 macrophages are more effective in the induction of the inflammatory response and clearance of Mycobacterium tuberculosis than M2 macrophages. Infected C57BL/6 mice generate a stronger cellular immune response compared with BALB/c mice. We hypothesized that infected C57BL/6 mice would exhibit a higher frequency and function of M1 macrophages than infected BALB/c mice. Our findings show a higher ratio of macrophages to M2 macrophages in the lungs of chronically infected C57BL/6 mice compared with BALB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The contradictory results reported by different groups using similar methodologies suggests that, in addition to species differences, there are strain and/or individual differences in macrophage responses to simulation. This has been substantiated by the findings of others; inbred strains of mice vary greatly in their ability to increase iNOS activity [16, 33]. Stimulation of bovine MDM with LPS and IFNγ resulted in 2-fold increases in NO activity when harvested from animals which were resistant to M. bovis but not from susceptible animals [23].…”
Section: Discussionmentioning
confidence: 75%
“…The contradictory results reported by different groups using similar methodologies suggests that, in addition to species differences, there are strain and/or individual differences in macrophage responses to simulation. This has been substantiated by the findings of others; inbred strains of mice vary greatly in their ability to increase iNOS activity [16, 33]. Stimulation of bovine MDM with LPS and IFNγ resulted in 2-fold increases in NO activity when harvested from animals which were resistant to M. bovis but not from susceptible animals [23].…”
Section: Discussionmentioning
confidence: 75%
“…The heterogeneity in phagocyte phenotype is also reflected in the relative balance of lymphocyte subsets in different granulomas in Mtb-infected macaques [ 38 ]. Finally, the manipulation of macrophage phenotypes in mice through the use of allergens, or the exploitation of different genetic backgrounds, impacts the ratio of M1/M2 type macrophage subsets and influences the bacterial burden [ 39 , 40 ].…”
Section: The Impact Of Host Cell Phenotype On Bacterial Burdenmentioning
confidence: 99%
“…It is reported that one-third of the world's population is infected with Mycobacterium tuberculosis ( MTB ); however, only 10% of the MTB infected population will develop TB disease during their lifetime. TB is mainly caused by MTB that primarily invades the lung phagocytes such as macrophages, neutrophils, monocytes, and dendritic cells [ 2 ]. In 90% of subjects infected with MTB (LTBI), the ensuing immune response arrests further the development of TB disease.…”
Section: Introductionmentioning
confidence: 99%